Typical and Atypical Clinics in COVID-19 (SARS-Cov-2) RT-PCR Positive Patients: A Multicenter Retrospective Study - Rıdvan Alagöz; Nurdan Acar; Evvah Karakılıç; Engin Özakın; Şeyhmus Kaya; Davut Kaplan; Volkan Ercan; Filiz Baloğlu Kaya; Çağlar Kuas; Onur Türkdoğan; Mustafa Emin Çanakçı (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
In this study, we sought to determine the consistency of symptoms in patients admitted to three high-volume emergency departments with a diagnosis of COVID-19 with the standard definition published by the Turkish Ministry of Health, and to examine the relationship between symptom type and clinical outcomes. This multicentre, retrospective, observational study included adult patients aged 18 years and over who tested positive for SARS-CoV-2 by RT-PCR in the emergency departments of three hospitals between 11 March and 31 December 2020. Presentation symptoms were classified as typical or atypical in accordance with the national COVID-19 guidelines dated 7 December 2020. Demographic characteristics, vital signs, laboratory results, comorbidities and clinical outcomes were compared between the two groups. A total of 5,274 patients were enrolled; 2,763 (52.4%) were male, and the median age was 63 years. Of these, 4,262 (80.8%) had typical and 1,012 (19.2%) had atypical presentations. Dyspnea was the leading complaint (38.7%), followed by cough (29.9%) and fatigue (20.6%). Patients in the typical group were older (median 64 vs. 60 years, p<0.001), had lower oxygen saturation (90% vs. 91%, p<0.001), and demonstrated higher inflammatory markers including CRP, D-dimer, LDH, and ferritin. Intensive care unit admission was more frequent in the typical group (10.1% vs. 3.2%, p<0.001), as was in-hospital mortality (10.5% vs. 3.0%, p<0.001). Approximately one in five COVID-19 patients presented to the ED with atypical complaints. It should be noted that atypical or asymptomatic patients in terms of clinical course may be missed with symptom-based screening alone. Patients presenting with typical symptoms, particularly those with dyspnea and underlying comorbidities, had considerably worse outcomes and warrant close monitoring.